Uruguay : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
The buffers built in the aftermath of Uruguay's 2002 banking crisis have shielded the financial sector from the effects of the global financial turmoil. Growth has been robust and the outlook continues to be favorable. However, inflation persists but capital inflows have improved, and policy measures have been taken in response. Uruguay exhibits no obvious signs of near-term domestic macrofinancial vulnerability. The external risks to the economy and the financial system come from a fragile global environment, and policy measures are recommended to reduce dollarization.